Bureaucracies’ Extended Arm in Co-creation: A Study of Institutional Complexity in the Context of Public Services - Rønshaugen, Marie; Sønderskov, Mette; Magnussen, Siv Fladsrud (Scandinavian Journal of Public Administration, 2024)
Co-creation, as a central strategy of the New Public Governance (NPG) paradigm, is deemed essential to address complex societal challenges. A qualitative, in-depth study was conducted to explore collaborative processes between the Norwegian Labour and Welfare Administration (NAV) and three external organizations. The aim of co-creation among these actors was to limit/prevent outsiderness by providing more individualized work inclusion services to young adults facing vulnerabilities. Our study examines collaborative processes between NAV and external actors in work inclusion efforts and explores how institutional complexity within NAV influences the potential for co-creation among these actors. We found that the bureaucratic logic of the Traditional Public Administration (TPA) within NAV forces external actors to engage in challenging, time-consuming procedures, turning them into bureaucracies’ extended arms rather than independent contributors of resources. Additionally, core principles of New Public Management (NPM), such as resource control and optimization, overshadow the importance of shared responsibility, equality, and knowledge sharing (NPG). With NAV as an example, the article demonstrates the importance of effectively managing institutional complexity in public organizations to succeed in co-creation. It contributes empirical and contextual examples of co-creation processes in the public sector, as the co-creation literature is still very theoretical, descriptive, and conceptual.